Why ethnicity and gender matters for fertility intention among married young people: a baseline evaluation from a gender transformative intervention in rural India - Tina Khanna; Murari Chandra; Ajay Singh; Sunil Mehra (BMC, 2018)
Abstract Background Social inequities in early child bearing persist among young married people, especially among tribal populations in India. Rural women belonging to tribal groups and those coming from poor households are more likely to give birth before age 18. This paper explores the connection between ethnicity, gender and early fertility intention among young married people in rural India. Methods The data is drawn from a cross sectional baseline evaluation of an intervention programme in rural India. A sample of 273 married young people was taken. Respondents were selected using systematic random sampling. Logistic Regression was used to assess the effect of being a tribal on early fertility intention and also to determine if covariates associated with early fertility intention differed by tribal status. Qualitative data was analysed using deductive content analysis approach. Results Bivariate and logistic regression results indicated that young married people from tribal communities had higher odds of planning a child within one year of marriage than non-tribals (OR = 1.47, p-value-0.079). Findings further suggest that early fertility intention among tribals is driven by gender factors and higher education and among non-tribals, higher education and awareness on contraception are key predictors. Among tribals, the odds of planning a child within one year of marriage was strongly associated with inequitable gender norms (OR = 1.94, p-value-0.002). Higher education showed significant positive association with non-tribals (OR = 0.19, p-value-0.014) and positive association with tribals (OR = 0.56, p-value-0.416). Qualitative investigation confirms that fertility desires of young married people are strongly influenced by gender norms especially among tribal populations. Conclusion Early child bearing was underpinned by complex ethnic factors and gender norms. Preference for early child bearing was seen most among tribal communities. Gender attitudes were a cause of concern especially among tribal groups. These results suggest that efforts to improve early child birth will require changing gender norms related to fertility among tribals as well as social equity issues including higher education among non-tribals and tribals.